Acculturation and English writing anxiety among indigenous students of Kerala - Reshma Das M; Binu Zachariah (Discover Education)
Abstract The impact of acculturation with reference to English language writing anxiety among the tribal students of Kerala is a less discussed topic in tribal education and language studies. The psychological changes, the cultural shifts and the caste/class discrimination that happen in an academic environment have to be identified using proper measuring tools. This paper analyses the English language classroom anxiety and writing anxiety among tribal students in Kerala and the impact these have on their English language writing performance. The paper is an attempt to evaluate the above-mentioned scenario in the light of the acculturation these students have to go through. This study helps to evaluate the condition of the students based on the fourth goal of the United Nations Sustainable Development (United Nations (2024, https://sdgs.un.org/goals/goal4 ). Data from 188 tribal school students have been collected and analyzed using Statistical Packages for Social Sciences to prove the assumptions of the study. The paper puts forward some recommendations that not only can improve the condition of these students but also ensure an inclusive learning environment.